Interactive effects between paylean™ (Ractopamine HCl) and dietary lysine on finishing pig growth performance, carcass characteristics and tissue accretion - Webster, M.J.; Goodband, Robert D.; Real, D.E.; Woodworth, J.C.; Marsteller, T.A.; Tokach, Michael D.; Unruh, John A.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 432 pigs were used to evaluate the effects of Paylean and dietary lysine on finishing pig growth performance, carcass characteristics and tissue accretion. The 12 dietary treatments included Paylean (0, 4.5, and 9.0 g/ton) and 4 levels of lysine. For pigs fed no Paylean, lysine levels were 0.60, 0.80, 1.00, and 1.20%. For pigs fed 4.5 or 9.0 g/ton of Paylean, lysine levels were 0.80, 1.00, 1.20, and 1.40%. The results indicate that pigs fed Paylean need at least 1.0% dietary lysine to optimize growth, carcass parameters, and tissue accretion.
Keywords: Swine; Paylean; Lysine; Finishing pigs; Accretion